Percutaneous cerclage wiring for reduction of periprosthetic and difficult femoral fractures. A technical note - Apivatthakakul,T. (Elsevier Limited, 2015)
Background: Combining closed reduction techniques with minimally invasive plate osteosynthesis (MIPO) or intramedullary nailing is a technically challenging procedure, especially when dealing with complex femoral fractures such as periprosthetic fractures. Cerclage wiring is a well known adjunct for fracture reduction and fixation. However, it is usually performed by open reduction, requiring wide surgical exposures, that results in soft tissue stripping. Objectives: To present how a novel cerclage wiring technique, employing a new percutaneous cerclage system, helped reduce a periprosthetic femoral fracture, fixed with MIPO, and a difficult proximal femoral fracture, stabilized with an intramedullary nail. Conclusion: Percutaneous wiring is an alternative reduction technique to facilitate the reduction and maintenance of difficult femoral fractures, which reduces the radiation exposure to the surgeon. © 2011 Elsevier Ltd. All rights reserved.